Printed Dielectrophoretic Electrode‐Based Continuous Flow Microfluidic Systems for Particles 3D‐Trapping. (15th January 2021) - Challier, Lylian; Lemarchand, Justin; Deanno, Catherine; Jauzein, Cecile; Mattana, Giorgio; Mériguet, Guillaume; Rotenberg, Benjamin; Noël, Vincent
Abstract: Inkjet‐printing is used to fabricate dielectrophoretic electrodes able to trap polystyrene (PS) microparticles as well as model planktonic cells. The possibility of rapid prototyping offered by inkjet‐printing allows the rational design of microchannels with tailored electric field distributions experienced by the suspended particles, which in turn provides a handle to drive them towards target regions. Specifically, this goal is achieved using two facing substrates constituting the bottom and the top walls of the channel, with a pair of interdigitated electrodes previously patterned by inkjet‐printing on each side. Influence of electrode polarization (magnitude and frequency of the input signal) is investigated both theoretically, by modeling the electric field distribution inside the channel, and experimentally using confocal fluorescence microscopy. The printed device is able to sort circulating PS particles as a function of their size, with diameters ranging from 0.5 to 5 µm, as well as to separate planktonic species according to their composition ( Alexandrium minutum versus Prorocentrum micans ). This work paves the way for the development of large‐area, microstructured dielectrophoretic electrodes able to separate the constituents of samples at flow rates up to 150 µL mn −1 . Abstract : Printed dielectrophoretic electrodes coupled to microfluidics are used to drive colloids toward a given channel location according to their size (500 nm to 5 µm‐radius polystyrene nanoparticles) and their chemical composition ( Alexandrium minutum versus Prorocentrum micans planktons) at high flow rate. The device architecture is designed by tailoring the electric field distribution with numerical modeling and fabricated by inkjet‐printing.